SACRED JOURNEYS AND SUSTAINABLE GROWTH: EVALUATING THE IMPACT OF RELIGIOUS TOURISM ON THE ECONOMIC DEVELOPMENT AND PROMOTION OF SIBEA-BEAAS A PREMIER DESTINATION IN SAMOSIR ISLAND, NORTH SUMATRA PROVINCE, INDONESIA. - Wiharjokusumo, Padriadi; Girsang, Dameria; Saragih, Novita Romauli; Karo-Karo, Selamat (Akademi Pariwisata Darma Agung, 2024)
This qualitative study explores the interplay between religious tourism and sustainable economic development in Sibea-bea, a potential tourist destination on Samosir Island, North Sumatra Province. Through in-depth interviews, participant observation, and document analysis, the research aims to understand how religious tourism can be a catalyst for economic growth while preserving cultural integrity and environmental sustainability. The study focuses on the pilgrimage practices, economic activities, and environmental policies that shape the sustainable development of Sibea-bea. It also examines the strategies employed by local stakeholders to promote Sibea-bea as a unique religious tourist destination within the global market. By analyzing the perceptions and experiences of both locals and tourists, the research seeks to provide insights into the effective management of religious sites that can contribute to the economy without compromising the locale’s sanctity and ecological balance. The findings are expected to offer a framework for policymakers and tourism developers to foster a symbiotic relationship between religious devotion and economic prosperity, ensuring the long-term viability of Sibea-bea as a sacred yet economically thriving destination.